Signaler le mensonge dans le Roman de Renart. Jeux et enjeux stylistiques - Valentine Eugène (Perspectives Médiévales)
Le Roman de Renart, a work whose date of composition (1175-1250) more or less coincides with that of an intense reflection on the sins of language (1190-1260), contains a great many falsehoods. It is surprising, however, that the storytellers introduce a discrepancy between the frequent representation of words that contravene the criterion of truth in the dialogues and the rare use of metadiscursive terms belonging to the morphological paradigm of lying. Cultivating a form of ambiguity, dialogues favour other terms which, absent from the normative texts, attenuate the moral significance of statements. Far from being limited to lexical surveys, this article is more generally interested in the various processes of euphemisation which, while avoiding naming the deviance, make it possible to indicate its existence.